A qualitative descriptive study of the contextual factors influencing the practice of emergency nurses in managing emerging infectious diseases - Stanley K. K. Lam; Enid W. Y. Kwong; Maria S. Y. Hung; Samantha M. C. Pang; Wai T. Chien (International Journal of Qualitative Studies on Health & Well-Being, 2019)
Purpose: Emergency nurses are engaged in the management of epidemic events that unfold along with the evolution of diseases. The goal of this study was to explore the contextual factors that inhibited the ability of emergency nurses to perform their duties in response to an outbreak. Methods: A qualitative descriptive design was used to explore the experiences and perceptions of emergency nurses. Participants were purposively recruited from 12 emergency departments in Hong Kong. Semi-structured face-to-face individual interviews were conducted with 26 emergency nurses. The audio-recorded interviews were transcribed verbatim and interpreted with a thematic analysis approach. Results: Four intertwined themes emerged from the analysis: resource constraints, threats of infection, ubiquitous changes and lingering uncertainties. These themes portrayed the constraints and challenges surrounding the work environment of emergency nurses. Conclusion: This study described the instabilities and vulnerabilities of the circumstances in which the emergency nurses were situated in during epidemic events. The findings shed light on the importance of hospitals and emergency departments in addressing both the technical problems and adaptive challenges that face emergency nurses during epidemic events.